A Study of the Defect in the Intention of Prayers and Its Relations with the Rule of “No Resumption” Based on Imam Khomeini’s Approach - Farahnaz Afzali Qadii (پژوهش‌نامه متین, 2022)
The daily prayer is a contractual composite with several parts and conditions,some of which are pillars and some not. Intention is one of the pillars of the dailyprayers. Defect in the intention is sometimes related to the prayer as a wholeand sometimes it is related to its constituting parts only. The main objective ofthis article is to study the viewpoints of some jurisprudents and Imam Khomeiniregarding the role of intention in prayers. Analytical-descriptive method has beenused in this research. The main question of this research is as follows: What isthe relationship between any defect in the intention of prayers and its invalidity?The findings of the research show that intention means “the performance of theprayers with the purpose of saying it and performing its constituting parts whichfollows the will to say the prayers”. Any defect in the intention of the prayeritself, leads to its invalidity. Regarding the constituting parts of the prayers, ifthe worshipper at the time of deciding to say the prayers decides to perform itsconstituting parts, the constituting parts will be parts of his mission, otherwise,they will not be parts of the prayers and the prayers will be invalid. If defect inthe intention is related to the parts that are pillars of the prayers, it will lead to itsinvalidity, but defect in the intention related to the parts that are not pillars, on thebasis of the “rule of no resumption”, will not lead to the invalidity of the prayers,but invalidates that particular part and if possible its resumption is mandatory. Butif the worshipper enters the next pillar of the prayers, on the basis of the said rule,it is not mandatory to compensate it and the prayers will be valid.